Effect of grain boundaries and crystal orientation on etching behavior of 12 µm thick rolled copper foil. (March 2023) - Zhao, Weichao; Feng, Rui; Wang, Xiaowen; Wang, Yongxiao; Pan, Yaokun; Gong, Benkui; Han, Xinjun; Feng, Tianjie
Abstract: The etching of rolled copper foil is a key process in the production of high-end Flexible Printed Circuit (FPC) boards, which is obviously affected by the microstructure. In this paper, Electron Back Scatter Diffraction (EBSD) was used to characterize the grain boundaries and crystal orientation of 12 µm thick rolled copper foil during etching. The research results show that High Angle Grain Boundaries (HAGBs) are preferentially etched in the initial stage of etching. Compared with the un-etched copper foil, the HAGBs proportion of copper foil etched for 6 min significantly decreases from 54.66 % to 39.92 %. With the increasing of etching time, the crystal orientation gradually becomes the main factor affecting the etching behavior. Compared with the copper foil etched for 6 min, the {001} crystal plane proportion of copper foil etched for 15 min increased from 26.04 % to 56.70 %, and {001} crystal plane has the higher etching resistance in acidic etching solution. Graphical Abstract: ga1 Highlights: The method of preparing EBSD samples of etched ultra-thin copper foil is proposed. The only sample is used to characterize the microstructure during etching. The HAGBs are preferentially corroded in the initial stage of etching. The {001} crystal plane has the higher etching resistance in acidic etching solution.